Do Single Men Smell and Look Different to Partnered Men? - Mahmut, Mehmet K.; Stevenson, Richard J. (Frontiers in Psychology, 2019)
Previous research indicates human body odor (BO) can signal kinship, sickness and genetic compatibility. Based on research indicating single males have higher testosterone levels than partnered males and that higher testosterone levels are associated with stronger smelling body odor, the current study aimed to determine if, by extension of previous findings, single males’ BO smells stronger than partnered males’ BO. Eighty-two heterosexual women aged 18 – 35 years rated the BO and faces of six different males also aged 18 – 35 years. Consistent with the hypothesis, single men’s BO smelled stronger than partnered men’s BO and single men’s faces were rated as more masculine than partnered men’s faces. The possible advantages of females being able to identify single males are addressed in the Discussion.